Repression upon Rachel Chu’s in Kevin Kwan’s Crazy Rich Asians - Deny Naufal Kurniawan; Ariya Jati (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
This study is about repression perceived by Rachel Chu, the main character in Kevin Kwan’s Crazy Rich Asians. The goal of this research is to describe repression in the light of the psychoanalytic defense mechanism repression. The researcher uses two data sources, namely the main data, which is Kevin Kwan Crazy Rich Asians novel published in 2013, and the supporting data, comprising books, websites, dictionaries, newspapers, and a number of novel-related articles. This research is a qualitative one; that is, the researcher adopts Sigmund Freud’s concept of defense mechanism especially repression to evaluate the data. The evaluation presents Rachel Chu’s state of id, ego, and superego in response to the situations surrounding her. The defense mechanism repression results in Rachel Chu’s persistence against stereotypes she cannot take, and also the impact of the repression on herself, or the people around her.Keywords: defense mechanism; repressions; education background; social status